A Descriptive Study of the Etiology and Outcome of Peripheral Vascular Injuries at the Aminu Kano Teaching Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Peripheral vascular injuries (PVIs) are infrequent but their management could be hampered by delayed presentation and fraught with untoward morbidity or death. Herein, we describe the factors contributing to the morbidity and mortality of PVIs in this environment.Materials and Methods:Data relating to patients with PVIs between March, 2012 and March, 2018 were retrospectively collected from case folders and analyzed.Results:The records of 16 patients were analyzed. There were 13 (76.9%) males and 3 (23.1%) females. The male/female ratio was 4.3:1. The median age was 30 years (range, 10–52). The median duration between injury and presentation was 2.5 days. Nine (56.3%) PVIs were secondary to stab wounds; two (12.5%) occurred in intravenous drug abusers while the others were each of different etiologies. The superficial femoral artery was the most frequently injured vessel (six cases; 37.6%). Fourteen (87.5%) patients required surgery ranging from patch arterioplasty to reversed saphenous vein interposition graft. Two (12.5%) patients were managed conservatively. The mean length of stay for the overall patient population was 11.7 days. Ten patients (62.5%) had surgical site infections (SSIs) causing prolonged hospital admission. There were three deaths (18.8%), all occurring in patients with co-morbidities like chronic kidney disease (CKD) and sepsis.Conclusion:PVIs were infrequent in this environment and presentation is delayed. Reasonable limb salvage rates are possible depending on the severity of ischemia. SSIs may suggest prolonged hospital stay. Mortality appears to be heightened if there are underlying co-morbidities. More patients would however be required to statistically correlate these findings.